Konsep Sistem Informasi Manajemen Organisasi dalam Pelayanan Kesehatan - Maharani, Ridha (AKADEMIK: Jurnal Mahasiswa Humanis, 2023)
The purpose of the research is to find the Concept of Organizational Management Information Systems in Health Services. Research method is a research that reviews literature using a number of sources selected based on standards of inclusion and exclusion of researchers. This research is a review of literature by doing searches and searches of libraries to produce articles on a particular research topic or problem. Research results One important component in the provision of medical services in the clinic is the health information system. Patient documentation becomes easier, operational efficiency increases, and decision-making becomes more accurate with integrated health information systems. Some of the other benefits of implementing a health information system include centralized patient data storage, inter-departmental integration, performance monitoring, and improved patient service. However, the use of SIK also faces issues such as costs, adjustment of procedures, data security, and user acceptance. Clinics can improve the efficiency and quality of services by understanding the advantages and disadvantages of Health Information Systems.